1996
DOI: 10.1074/jbc.271.9.4813
|View full text |Cite
|
Sign up to set email alerts
|

HER4-mediated Biological and Biochemical Properties in NIH 3T3 Cells

Abstract: The EGF receptor family of tyrosine kinase growth factor receptors is expressed in a variety of cell types and has been implicated in the progression of certain human adenocarcinomas. The most recent addition to this family of receptors, HER4, was expressed in NIH 3T3 cells to determine its biological and biochemical characteristics. Cells expressing HER4 were responsive to heregulin beta2 as demonstrated by an increase in HER4 tyrosine phosphorylation and ability to form foci on a cell monolayer. HER4 exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Moreover, phosphorylation of ErbB4 at Tyr 1056 creates a canonical binding site for the PI3K regulatory subunit [35,36]. Thus it is plausible to postulate that the PI3K pathway is required for ErbB4 coupling to IL-3-independent proliferation in BaF3/EGFR + ErbB4 cells, and that differential ErbB4 coupling to the PI3K pathway may underlie the functional differences between ErbB4 agonists and antagonists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, phosphorylation of ErbB4 at Tyr 1056 creates a canonical binding site for the PI3K regulatory subunit [35,36]. Thus it is plausible to postulate that the PI3K pathway is required for ErbB4 coupling to IL-3-independent proliferation in BaF3/EGFR + ErbB4 cells, and that differential ErbB4 coupling to the PI3K pathway may underlie the functional differences between ErbB4 agonists and antagonists.…”
Section: Resultsmentioning
confidence: 99%
“…ErbB4 phosphorylation on Tyr 1056 creates a binding site for the PI3K regulatory subunit [30,3537]. Because we had demonstrated that the PI3K/Akt signalling pathway appears to be critical in specifying the effects of stimulation with ErbB4 agonists and antagonists, we postulated that Tyr 1056 is critical for NRG2β stimulation of IL-3 independence in BaF3/EGFR + ErbB4 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the mechanisms by which HRGβ1 overcame fulvestrant action were subtly different in the HER2 low-expressing and HER2-overexpressing cell lines. In the MCF-7 and T47D cells, fulvestrant selectively enhanced the ability of HRGβ1 to phosphorylate ErbB4 at Y1056, a PI3K-p85 recruitment site [56], and promote AKT signalling activity, whereas in the BT474 and MDAMB361 cells, it was the HRGβ1-induced ErbB4 Y1284 SHC recruitment site [56] and ERK1/2 phosphorylation that were selectively augmented by antihormonal treatment. The differential ErbB4 phosphorylation and downstream pathway recruitment may reflect the expression of alternative ErbB4 isoforms in these cells, with the CYT-2 isoform, which lacks the Y1056 PI3K binding consensus site, potentially being preferentially expressed in the ErbB2-overexpressing cell lines [57].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the oncogenic transformation capacity is not identical among members of the EGFR family. Cohen et al [39] demonstrated that any combination of EGFRs was able to induce in vitro transformation of NIH:3T3 cells. In spite of this, EGFR/c-erbB-2 was the only heterodimer capable of inducing in vivo transformation into a tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%